Usefulness of artificial vascular graft for venous reconstruction in liver surgery - Orimo, Tatsuya; Kamiyama, Toshiya; Yokoo, Hideki; Kakisaka, Tatsuhiko; Wakayama, Kenji; Tsuruga, Yosuke; Kamachi, Hirofumi; Taketomi, Akinobu (World journal of surgical oncology, 2014)
The purpose of this study was to evaluate the results of hepatectomy with inferior vena cava or hepatic vein resection, followed by vessel reconstruction with an artificial vascular graft. From 2000 to 2011, 1,434 patients underwent several types of hepatectomy at our institution. Of these, we reviewed the cases of eight patients (0.56%) who underwent hepatectomy with inferior vena cava or hepatic vein resection and subsequent reconstruction using an expanded polytetrafluoroethylene (PTFE) graft. We resected the inferior vena cava in six patients and the hepatic vein in two patients. All eight patients underwent subsequent reconstruction using an expanded PTFE graft. The median operative time was 443 minutes and the median blood loss was 2,017 mL. The median postoperative hospital stay period was 18.5 days and the in-hospital mortality rate was 0%. Complications occurred in four patients: two patients experienced bile leakage, one experienced a wound infection, and one experienced pleural effusion. The two patients who experienced bile leakage had undergone reoperation on postoperative day 1. No complication with the artificial vascular graft occurred in these eight cases. Histological invasion to the replaced inferior vena cava or hepatic vein was confirmed in four cases. All artificial vascular grafts remained patent during the observation period. Hepatectomy combined with inferior vena cava or hepatic vein resection, followed by reconstruction with an expanded PTFE graft can be performed safely in selected patients.